Towards a missional liturgy - Wepener, C (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
In this article the central question being explored is ‘what is a missional liturgy?’ The exploration is conducted by making use of data and insights obtained from the Southern African Partnership for Missional Churches (SAPMC). After an introduction to the theme as well as the SAPMC-process, the analyzed data is presented. In conclusion some observations are made in an attempt to provide preliminary contours for attempts to answer the initial question.